2020
DOI: 10.7759/cureus.12264
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypothyroidism Among Carpal Tunnel Syndrome Patients at a Hospital in Saudi Arabia

Abstract: IntroductionPatients with carpal tunnel syndrome have a high prevalence of hypothyroidism, therefore, it is recommended to assess thyroid function routinely in patients with carpal tunnel syndrome. This study aims to determine the prevalence of hypothyroidism among carpal tunnel patients and to relate carpal tunnel in hypothyroidism to other socio-demographic factors. MethodsThis was a retrospective study carried out in King Fahad Medical City (KFMC) in Riyadh, Saudi Arabia. A total of 422 samples were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…As mentioned above, a possible explanation for unrelated clinical symptoms with electrodiagnostic grading in hypothyroidism patients may be the role of thyroid replacement therapy in reducing symptoms, regardless of its effect on electrodiagnostic parameters. Aldaghri et al, reported more than two-thirds of those with hypothyroidism were asymptomatic and the presence of thyroid abnormality doesn't affect the duration of carpal tunnel syndrome (Aldaghri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, a possible explanation for unrelated clinical symptoms with electrodiagnostic grading in hypothyroidism patients may be the role of thyroid replacement therapy in reducing symptoms, regardless of its effect on electrodiagnostic parameters. Aldaghri et al, reported more than two-thirds of those with hypothyroidism were asymptomatic and the presence of thyroid abnormality doesn't affect the duration of carpal tunnel syndrome (Aldaghri et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study was done in Libya of an epidemiological study of CTS among pregnant women and it showed that most of the cases are improved by home physiotherapy 79.7% medications improved the cases by 20.3%, 37.8% of cases reported symptomatic relief after massage, 28.4% from rest and 4% from activity. Reducing weight before pregnancy, avoiding repetitive tasks that can aggravate CTS was recommended (Aldaghri et al, 2020).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Patients with severe symptoms can be treated by surgical decompression which provides a good outcome. However, surgical intervention is rarely indicated in pregnant patients (Aldaghri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A confounder in the relation between dyslipidemia and CTS that must be taken into account in epidemiological studies is hypothyroidism, as on one side, CTS is more frequent in patients with this medical condition, and on the other side, dyslipdemia, hyperinsulinemia and large waist circumference are present even in mild hypothyroidism [ 82 ]. In some studies, the body mass index (BMI) was the link between hypothyroidism and CTS [ 83 , 84 ]. Even in euthyroidism, the TSH level in the upper range significantly increases the chances of MetS [ 85 ].…”
Section: Insulin Resistance Dyslipidemia Inflammatory and Oxidative M...mentioning
confidence: 99%